STUDI PENANGGULANGAN BANJIR DI KALI BATAN KABUPATEN KEDIRI - Moch Adib Kuncoro; Sigit Winarto; Yosef Cahyo Setianto Purnomo (Kadiri University, 2018)
Kali Batan is one of the tributaries of the Brantas River, which is located in the Kediri Regency. In the last few years, there have been floods in Kali Batan. In the Batan watershed, there are three stations that are considered to represent the percentage of the effect of the calculation of the maximum daily rainfall intake, which is 83.11mm. From the maximum daily rainfall, the result is-0.9546. From the calculations in the Smirnov-Kolmogorov method distribution suitability test, it shows that the highest value of Î”max is = 0.126, with Î± = 5% and n = 20, the value Î”critical = 0.304. So it can be concluded that Î”max <Î”critical so that the Log Pearson type III distribution can be accepted. From the measurement of the Batan watershed at the upstream review point, the result is 3.206 m3 / s. From the measurement of the Kali Batan watershed at the downstream point, the results obtained were 202.475, using equations (2-14) to (2-17), the design flood hydrograph obtained 3,825 m3 / s. The value of the net rainfall intensity value (25 years ) entered into the coordinates of the Nakayasu Synthetic Hydrograph, then the flood discharge design Q25th is obtained.Kali Batan merupakan salah satu anak sungai Kali Brantas yang terletak di Kabupaten Kediri. Beberapa tahun terakhir terjadi banjir di Kali Batan. Â Pada DAS Batan terdapat tiga stasiun penakar hujan yang dianggap mewakili dengan prosentase pengaruh perhitungan pengambilan curah hujan harian maksimum didapatkan sebesar 83,11mm. Dari curah hujan harian maksimum didapatkan hasil- 0,9546. Dari perhitungan pada Uji kesesuaian distribusi metode Smirnov-Kolmogorov menunjukkan bahwa nilai tertinggi Î”max adalah = 0,126, dengan Î± = 5 % dan n = 20 didapatkan harga Î”kritis = 0,304. Maka dapat disimpulkan bahwa Î”max< Î”kritis sehingga distribusi Log Pearson tipe III dapat diterima. Â Dari pengukuran DAS Batan pada titik tinjau hulu didapatkan hasil3,206 m3 /dt. Dari pengukuran DAS Kali Batan pada titik hilir didapatkan hasil202,475, denganmenggunakan persamaan-persamaan (2-14) sampai dengan (2-17), hidrograf banjir rancangan diperoleh 3,825 m3 /dt.Besarnya nilai intensitas curah hujan netto (kala ulang 25 th) dimasukkan ke dalam koordinat Hidrograf Sintetis Nakayasu maka didapatkan debit banjir rancangan Q25th.